2015
DOI: 10.1016/j.jvs.2015.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between histologic features and outcomes of carotid revascularization for radiation-induced stenosis

Abstract: Our radiologic and histologic analyses revealed that advanced RICS is often accompanied by formation of vulnerable plaque. CEA can prevent undesirable late outcomes in such cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…The length of radiation induced stenosis segment has not been commonly evaluated. Sano N et al showed that stenosis lengths in CCA were significantly longer in the radiation induced stenosis group then in the non-irradiated patients with atherosclerotic stenosis (32.8 +/− 30.0 mm vs 6.9 +/− 5.1 mm) [20]. This is close to the values found in our study, where the mean length of CCA stenosis was 31.16 +/− 10.60 mm.…”
Section: Discussionsupporting
confidence: 90%
“…The length of radiation induced stenosis segment has not been commonly evaluated. Sano N et al showed that stenosis lengths in CCA were significantly longer in the radiation induced stenosis group then in the non-irradiated patients with atherosclerotic stenosis (32.8 +/− 30.0 mm vs 6.9 +/− 5.1 mm) [20]. This is close to the values found in our study, where the mean length of CCA stenosis was 31.16 +/− 10.60 mm.…”
Section: Discussionsupporting
confidence: 90%
“… 19 Occurrences of transient ischemic attacks or ischemic stroke have been well-documented due to the atherosclerotic changes observed in the irradiated vessels. 20 The main mechanisms of radiation-induced CAS include direct damage to the vessel, accelerated atherosclerosis, intimal proliferation, necrosis of the media, and peri-adventitial fibrosis. 21 , 22 Radiation-induced plaque and arterial wall thickening, which is histologically comparable with spontaneous atherosclerosis, tends to develop in the radiotherapy fields and can even occur in the cohort without the other risk factors of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism for carotid stenosis is not clear 29 . Injury to microvasculature may be the most important mechanism for injury in the large arteries 7 . Further research needs to be conducted in this area.…”
Section: Discussionmentioning
confidence: 99%
“…However, late complications, such as those reported in our previous work (optic neuropathy, brachial plexus injury and brain necrosis) 4 6 , have shown an increasing problem for RT treatment of NPC. While commonly used to prevent nodal metastasis, RT contributes to atherosclerosis of the irradiated vessels and increases the risk of vascular stenosis, which may lead to transient ischemic attacks (TIA) or ischemic stroke 7 .…”
Section: Introductionmentioning
confidence: 99%